KORELASI NILAI OPTICAL NERVE SHEATH DIAMETER DENGAN LENGTH OF STAY ICU PADA PASIEN PASCABEDAH OTAK DI RSUP HASAN SADIKIN BANDUNG - Wardana, Artha Wahyu; Sudjud, Reza Widianto; Aditya, Ricky (Jurnal Anestesi Perioperatif, 2025)
Background: Elevated intracranial pressure (ICP) is a common complication after craniotomy, often causing decreased consciousness, ventilator dependence, and prolonged ICU stay. Invasive ICP monitoring carries risks, while non-invasive methods such as optic nerve sheath diameter (ONSD) measurement via ultrasonography offer a promising alternative. This study aimed to examine the correlation between ONSD and ICU length of stay (LOS) in post-craniotomy patients.Methods: A prospective observational study was conducted at the ICU of Dr. Hasan Sadikin General Hospital, Bandung, from February to April 2024. Post-craniotomy patients admitted to the ICU were included. ONSD was measured 12–24 hours after ICU admission. Data collected included ONSD, demographics, preoperative clinical status, and ICU records. The relationship between ONSD and ICU LOS was analyzed using Pearson correlation and multivariable analysis.Results: Thirty-three patients were included (mean age 48.2 years; 60.6% male). Median preoperative GCS was 10.8, and 54.5% were ASA III/IV. ONSD correlated positively with ICU LOS (r = 0.636, p < 0.001). Multivariable analysis showed that ONSD ≥ 5.0 mm was independently associated with prolonged ICU stay (≥7 days) after adjusting for GCS and postoperative complications.Discussion: A larger ONSD, reflecting higher ICP, was moderately associated with longer ICU stay, suggesting that non-invasive ONSD measurement can serve as a useful marker for resource utilization. However, further studies with larger cohorts are needed to validate its predictive role.Conclusion: ONSD measurement is a reliable non-invasive parameter that shows a significant correlation with ICU length of stay in post-craniotomy patients.